Gender Equality Perspective of Asghar Ali Engineer: Challenges and Opportunities for Theological Feminists - Melta Adelia Putri Kurniandi (Pusat Studi Gender Universitas Jember, 2024)
Gender equality in the Islamic context is in deep focus, especially through the lens of feminist theology. This article explores the views of Asghar Ali Engineer, a Muslim activist, who advocates the need to treat women as equals to men and redefine sharia law regarding gender issues. The main focus is on the challenges and opportunities facing feminist theology in Islam, with an emphasis on the concept of gender equality and its impact on Muslim women. This research adopts a qualitative approach, analyzing and exploring data from key works such as